Forests of the Mediterranean region: gaps in knowledge and research needs - Scarascia-Mugnozza, Giseppe; Oswald, Helfried; Piussi, Pietro; Radoglou, Kalliopi (Forest Ecology and Management, 2000)
Mediterranean forests are characterised by a remarkable set of features that make them naturally and aesthetically attractive, on the one hand, but also quite fragile, on the other, therefore calling for careful strategies for their conservation and management. An exceptionally large variation of environmental conditions characterises the Mediterranean countries, where the environment can limit forest growth and succession but can also give rise, more often than it is supposed, to lush, mesic forest ecosystems, similar to those of central Europe. Moreover, Mediterranean forests contain an ample, plant and animal biological diversity, exempli®ed by the large number of tree species as compared to Nordic forests, and by their relatively high genetic variability due to the survival of many conifer and broadleaf species in southern European refuges, during the glacial periods. Another peculiar aspect of this region is the long-lasting manipulation of trees, forests and landscapes, since ancient times, with the diffusion all over the Mediterranean basin of such species as Pinus pinea, Cupressus sempervirens, Castanea sativa, and Quercus suber. The harsh and unpredictable climate, the dif®cult socio-economic conditions and the history of over-exploitation of the Mediterranean forests require that a scienti®cally sound conservation strategy and a locally-tailored sustainable management should be implemented. In particular, the need for identifying those silvicultural and management strategies appropriate for southern European forests should be stressed. Obviously, this consideration will have important effects on the de®nition of criteria for sustainability and eco-certi®cation. Also, social issues should be considered key factors for effective forest conservation in the Mediterranean region, otherwise it will be impossible to control forest ®res and landscape degradation. Based on these considerations a number of research priorities are discussed, with special consideration to possible impacts that global change may have on Mediterranean forest ecosystems.
Keywords: Biodiversity; forest ecosystems; Mediterranean Region; silviculture; sustainable management